RELATIONSHIP BETWEEN FAMILY SUPPORT AND SELF-CARE AMONG NON-HEMORRHAGIC STROKE PATIENTS - Muhammad Risal; Adrian Sali (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Stroke has several impacts, namely physical limitations and disabilities in self-care, stroke also causes stress and depression. By because it requires family support as a support system, family support can independently train and motivate family members who have suffered a stroke to perform self-care without depending on others. Objectives: This study aimed to determine the relationship between family support and self-care in non-hemorrhagic stroke patients at the Polyclinic Neurological of Lagaligo I Hospital, East Luwu Regency. Methods: This research was conducted at the neurology polyclinic of hospital I Lagaligo, East Luwu Regency from July to August 2020. The design of this study used an analytical survey with a cross sectional approach. The number of samples was 39 respondents with proportional random sampling technique. Data analysis used the Spearman Rank correlation statistic test with a value of = .05. Results: The results of the study with the Spearman rank test showed that the p-value (.000) was significantly lower than .05 or (ρ˂α), so there was a relationship between family support and self-care in non-hemorrhagic stroke patients at the Neurological polyclinic Hospital I Lagaligo, East Luwu Regency. Conclusion: The conclusion of this study is that there is a relationship between family support and self-care in non-hemorrhagic stroke patients and suggestions for nurses in the Neurology Polyclinic Room are expected to provide information and be able to provide nursing education, especially about family support with self-care in patients who have had non-hemorrhagic strokes.